The relevance of the hip extensor muscles to low back pain in elite female field hockey players - M. Wege; M. M. Bester; L. C. Crous (AOSIS, 2006)
Low back pain (LBP) is a common complaint among field hockey players.  Only a few of the risk factors for LBP have however been assessed on these players.  These include trunk strength and lumbosacral range of motion.  The aim of the literature review was therefore to investigate the reports of LBP among elite female field hockey players, focusing on risk factors for LBP, biomechanical aspects of field hockey, muscle imbalance and the role of the gluteus maximus (GM) muscle in the development of LBP.  The literature indicated a strong link between LBP and GM weakness.  More recent research supports this concept and clearly stated that female athletes with GM weakness are at risk for the development of LBP.  Considering that the biomechanical aspects and unique requirements of field hockey indicate hip extensor involvement, as well as the association between LBP and GM weakness, further investigation is warranted into the hip extensor muscles of field hockey players.